Variability of Morphological Parameters of Diospyros lotus L. Flowers - Grygorieva, Olga; Ilyinska, Antonina; Zhurba, Mykhailo; Vergun, Olena; Ercisli, Sezai; Hauptvogel, Pavol; Brindza, Ján (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2023)
The morphological variability of the male and female flowers of 23 date plum (Diospyros lotus L.) genotypes found together at date plum collection in Arboretum Mlynany (Slovak Republic) was investigated. The collection consists of seed-propagated genotypes, which were established in 1970 with introduced seeds from different countries. Results showed that male and female flowers of D. lotus genotypes differed from each other in terms of shape and size. According to the morphological analysis, several features were found variable both within and between different plants. Moreover, significant differences in the colour of their corolla were detected. Female and male flowers of D. lotus genotypes were grouped according to the absolute parameters of flowers, and five (male flowers) and three (female flowers) clusters were identified. The degree of affinity between species was assessed using values of Euclidean distance. Using the principal component analysis, female and male flowers were separated into groups with similar morphological parameters. Our investigation has extended the understanding of the morphological features of D. lotus flowers as compared to the previously published data, which were limited only to a short description.